IMPLEMENTASI KURIKULUM HOLISTIK-INTEGRATIF UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SDIT LHI - Hidayatul Muamanah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2020)
Integrative Holistic Education is an education that arises because one of the problems is due to the concerns of Islamic education thinkers about the dichotomy of science so that many children will be born who are smart but do not care about the surrounding environment. The purpose of this research is to explain how the implementation of integrated holistic education at SDIT LHI and the implications of the application of integrated holistic education curriculum at SDIT LHI. This research is a field research study with a qualitative approach to interview, observation and documentation data collection techniques and analyzed with the Milles Huberman model. The results show that the implementation of the Integrative Holistic Education curriculum has been carried out at SDIT LHI which contains 7 literacy and 7 M Integrated Learning, also adopted the 2013 curriculum. The purpose of implementing this curriculum is to shape students into humans who are not only intelligent but have skills and care with the environment in which students are located remembering their duties as servants and caliphs in the world. Using the learning model sure is fragmented, integrated, shared, conected, webbed, networked. Giving Islamic values ​​through activities such as tadabur Al-Qur'an, alms, so that students become the foundation and can be used as provisions in the future.